Cardiovascular Diabetology - Fisman, Enrique; Westermeier, Francisco; Tenenbaum, Alexander; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Cardiovascular Diabetology considers manuscripts on all aspects of the diabetes/cardiovascular interrelationship and the metabolic syndrome; this includes clinical, genetic, experimental, pharmacological, epidemiological and molecular biology research.
Keywords: Diseases; Blood-vessels$1 (BDiseases.s; Cardiology; Diseases; Angiology; Cardiology